Efeitos espaço temporais da poluição pontual e não pontual em uma bacia hidrográfica subtropical : ecohidrologia como ferramenta de controle - Gatti Junior, Pedro (2015)
Contaminants are introduced into aquatic ecosystems, both from point and diffuse sources and usually are deposited in the sediments of lakes and reservoirs. The input of diffuse pollutants in the environment is of difficult control and identification, while the control of point sources is more efficient because they are easily identified. However, the frequent discharges of effluents, althought undergoing treatment, may change the input of elements and substances in a given region. The aim of this study was to assess the spatial-temporal influence of point and non-point source pollution on the characteristics of surface water and sediment in a watershed with well-marked seasons. In addition, concepts and attempts at ecosystems restoration in different regions were reviewed in order to understand the main drivers of abiotic-biotic regulation among watersheds and aquatic ecosystems, based on the principles of Ecohydrology. For this purpose, the concentrations of Cd, Cr, Fe, Ni, Zn, Pb, Al, Cu, Mn, Hg, As, Se, total phosphorus, total nitrogen and ions in water and sediment were examined. Furthermore, levels of metals (Al, Fe, Mn, Cu, Zn, Hg and As) in the sediment profile of stations under of the influence of different impact were evaluated. This study showed that the point source pollution promote a high load of contaminants in sediment, regardless of the season. Furthermore, the point pollution sources seem to be spatially and temporally the main cause of reservoir sediment chemical composition due its frequent effluent release. This study also indicates that, despite several biogeographical differences, hydrology seems to be the main factor that controls the primary and secondary production and sustainability in rivers and lakes (reservoirs). In conclusion, the hydrology in the tropics seems to decrease the expected effects of a higher temperature. Therefore, to increase resilience in tropical freshwaters integrated actions according to hydrological stages are highly recommended.